The effect of warm ginger on the frequency of nausea and vomiting among pregnancy women - Ariyanti, Ririn; Febrianti, Selvia; Khariani, Zulfa Rahmalia; Sulistyowati, Tantry (Gaceta Médica de Caracas, 2022)
Introduction: Nausea and vomiting occur commonly during pregnancy and cause inconvenience among pregnant women. Non-pharmacological therapy with warm ginger was used in this quantitative study to relieve nausea and vomiting in pregnant women. The study aimed to determine the effect of using warm ginger on nausea and vomiting in pregnant women.